As cotas de gênero nas eleições brasileiras - Carvalho, Ana Paula Giamarusti (2020)
The theme of this research project is the gender quotas in elections in Brazil from the analysis of the laws and data of electoral elections in an empirical perspective. The main aspects related to women's candidacies were examined, such as campaign funding and women's conquest of political rights, as well as the experiences of some countries on the subject, as well as the jurisprudence of the Supreme Court and the Superior Electoral Court that implemented solutions and criteria for the application of electoral laws and resolutions. With the presentation of the data regarding the candidacies registered and elected, it is finally possible to understand the results achieved by the gender quota laws in the Brazilian elections.